Undergraduate pharmacy students' motivations, satisfaction levels, and future career plans - Alhaddad, Mahmoud S. (J Taibah Univ Med Sci, 2018)
OBJECTIVES: This study aims to evaluate undergraduate pharmacy students' reasons for joining the pharmacy program, their levels of satisfaction regarding their choice, and their future career plans. METHODS: A cross-sectional research design was adopted using a non-probability convenience sampling technique. All undergraduate pharmacy students at one public university in KSA were invited to participate in the study. RESULTS: A total of 398 participants responded to the questionnaire. Family influence (66.6%), seeking a job with diverse opportunities (81.7%), and the desire to work in a health-related profession (83.4%) were the main reasons for studying pharmacy. Only 58% of respondents affirmed that, given the chance to choose their undergraduate program again, they would still choose pharmacy. Working as a hospital clinical pharmacist was the most popular future career plan, cited by 83.2% of respondents. CONCLUSION: There is a need to guide high school students regarding their choice of undergraduate programs, and for these students to be made aware of the challenges and opportunities of studying pharmacy. This can be achieved by organizing a one-day pharmacy orientation program introduced to students during their high school education.